THE EFFECT OF SELF-COMPASSION ON DEPRESSION, ANXIETY, AND STRESS MEDIATED BY PERCEIVED BODY IMAGE IN PEOPLE WITH MOBILITY IMPAIRMENT AND DISABILITY IN PHRAE PROVINCE - WONGWAN, SIJUTA; VARMA, PARVATHY (Scholar: Human Sciences, 2022)
This study examined the direct and indirect effects of self-compassion on perceived body image, depression, anxiety, and stress. The indirect effect was examined with perceived body image as the mediating factor. The study also examined the differences between males and females in self-compassion, perceived body image, depression, anxiety, and stress. The study included 128 participants who are people with mobility impairment and disability from Phrae province. The study applied path analysis via multiple regression analysis. An independent t-test was conducted to study the gender difference. Four separate questionnaires were administered. A demographic questionnaire, Self-compassion Scale, was used to measure self-compassion, and Body Appreciation Scales-2 was used to measure perceived body image. Depression, anxiety, Stress Scale-21 was used to measure depression, anxiety, and stress. The study found that self-compassion had a significant direct and indirect effect on perceived body image, depression, anxiety, and stress. The finding showed there was no significant difference between males and females in regard to all areas of the study.